Shift of radiotherapy use during the first wave of the COVID-19 pandemic?: An analysis of German inpatient data - Medenwald, Daniel; Brunner, Thomas B.; Christiansen, Hans; Kisser, Ulrich; Mansoorian, Sina; Vordermark, Dirk; Prokosch, Hans-Ulrich; Seuchter, Susanne A.; Kapsner, Lorenz A.; Balig, Julien; Bienzeisler, Jonas; Bürgy, Daniel; et al. (Strahlentherapie und Onkologie, 2022)
Covid-19 pandemic, lockdown, radiotherapy, Germany, admissions
Members of the MII research group: Julien Balig, Daniel Bürgy [und viele weitere]
Published online: 07 January 2022